The Implementation of the Use Top-Down And Bottom-Up in Teaching Listening Comprehension on Third-Grade Students of MTS Ma’arif Ketegan Tanggulangin - Rusmawati, Dewi; Mandarani, Vidya (Indonesian Journal Publisher, 2023)
This research is aimed to analyze how is the teacher’ implementation in the use of the Top-Down and Bottom-Up in teaching Listening comprehension. The location where the researcher taken place were at MTS Ma’arif Ketegan Tanggulangin, the research subject was the English teacher of the third-grade students who taught 3 classes. In addition, the research method of qualitative descriptive was used in this research by doing class observation and interview. The results of this research were shown that Song by Maher Zain was using as the teaching media. Furthermore, in applying the Top-down strategy, the English teacher used several implementations such as: design a discourse schema, use key terms, Infer the text's environment, Infer the participants' roles and objectives, make inferences about causes and effects, and Prepare for questions about the topic or scenario. Meanwhile for the Bottom-up strategies. First, the teacher taught the vocabulary that will be utilized in the listening activities. Then, all students were given a sheet to do the exercise. Finally, the English Teacher played the audio, and the students had to complete the activity based on what they had heard.